An Analysis of Anxiety Speaking English in Online Learning using Zoom Cloud Meeting on EFL Students - Putri Oktarina; Anita Dewi Ekawati (UICELL, 2022)
Zoom Cloud Meeting is an application that is widely used for online learning, this application makes it easy to communicate directly virtually. When online learning is taking place using the Zoom Cloud Meeting application, many students feel anxious about speaking. This is because when lecturers ask students, many do not respond and they are afraid to speak. This study aims to find out the factors that influence students’ anxiety when speaking through zoom meetings. In this study, researchers used a questionnaire adapted from McCroskey (1970). The respondents of this study consisted of 104 EFL students who were in around JABODETABEK. Then the data were analyzed using descriptive statistics through IBM SPSS Statistics 26. The results of this study are that more students experience feel anxiety and fear when speaking English through Zoom Meetings when learning online. The findings of this study are to encourage EFL students to speak English without anxiety and improve their speaking skills in public or online classes. Keywords: Zoom Cloud Meeting, Online learning, Anxiety speaking